THE EFFECT OF SELF STRETCHING ON PAIN LEVELS DUE TO PIRIFORMIS SYNDROME AT TERAS HEALTH CENTER, BOYOLALI DISTRICT - Salmi, Umi; Sari, Dwi Rosella Komala (Academic Physiotherapy Conference Proceeding, 2021)
Background: Pain in the lower back is a common case experienced by most people in the world and one of the global health problems and identified quite high prevalence among the productive age. Piriformis syndrome often cause of misdiagnosis of LBP and sciatica secondary to entrapment of the sciatic nerve in the piriformis muscle by the greater degree of sciatica. Piriformis Syndrome result the pain in the gluteal area, piriformis muscle spasm, decreases gluteal muscle strength and decreases functional activities. Physiotherapy management for Piriformis Syndrome can be done using stretching modalities. Research Objectives: to determine the effect of self stretching on the degree of pain due to piriformis syndrome at Teras Health Center, Boyolali Regency. Research Methods: This study used a case study. There were 5 people who met inclusion criteria. Pain was measured by VAS that confirmed after treatment. The demography data age, body mass, and bodymass index, gender, and grade of OA. Result: The pain showed decreased between pre-test and post-test after treatment. Conclusion: Self stretching was giving beneficial to reduce pain in individuals with piriformis syndrome.